A coleta seletiva como instrumento propulsor da gestão do consórcio de resíduos sólidos na região metropolitana do Cariri-Ceará - Batista, Vanda Lucia Roseno [UNESP] (2015)
The regionalized management of solid waste in the metropolitan area of Cariri Cearense aims to build a consortium landfill, alternative considered important to dispose the waste. Accordingly, it should be integrated into the incentive policy of institutionalized selective collection in consortiums cities. Implement waste segregation system implies lower amount and the cost of tons of waste to be disposed in the regional landfill, include scavengers who live and survive in the dumps and strengthen their organization. Therefore, the research suggests a participatory selective collection system, supportive, cooperative and integrated that meets the needs, local and regional. This proposal responds to the central aim of the thesis, namely, proposing a system of selective collection with social participation from the reality of the place. To this end, it carried out quantitative and qualitative research, through questionnaires and workshops. The process took place in three rounds on which was attended by stakeholders involved directly in the process, namely: collectors, community, business people, teachers and administrators. For each segment were applied 30 questionnaires. For that Delphi technique was adapted. The spatial area of research is made up of six cities: Crato, Juazeiro, Barbalha, Nova Olinda, Santana do Cariri and Altaneira, all located in the southern region of Ceará. The theoretical map was based on the new concepts introduced by the National Policy on Solid Waste. It is understood that the selective collection system with the participation of organized collectors and based on the principles of social economy breaks with the management collect, transport and dispose the waste in open dumps, as these should be eliminated by 2018. Thus the segregation of waste effectively contribute to the shared management of municipal solid waste in view of the National Policy on Solid Waste